The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/bit.20730
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the structural properties and rate of hydrolysis of cotton fibers during extended enzymatic hydrolysis

Abstract: An extended enzymatic hydrolysis of cotton fibers by crude cellulase from Trichoderma pseudokoningii S-38 is described with characterization of both the enzyme changes of activities and cellulose structure. The hydrolysis rates declined drastically during the early stage and then slowly and steadily throughout the whole hydrolysis process the same trend could be seen during the following re-hydrolysis process. Morphological and structural changes to the fibers, such as swelling, frequent surface erosion, and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 69 publications
6
62
0
2
Order By: Relevance
“…The crystallinity index (CrI) were determined based on the equation shown below (Kim and where I002 is the intensity of the diffraction from the 002 plane at 2θ=22.6° and Iam is the intensity of the background scatter measured at 2θ=18.7°. It is known that the I002 peak corresponds to the crystalline fraction and the Iam peak corresponds to the amorphous fraction (Wang et al 2006).…”
Section: Determination Of Crystallinity Index (Cri)mentioning
confidence: 99%
See 1 more Smart Citation
“…The crystallinity index (CrI) were determined based on the equation shown below (Kim and where I002 is the intensity of the diffraction from the 002 plane at 2θ=22.6° and Iam is the intensity of the background scatter measured at 2θ=18.7°. It is known that the I002 peak corresponds to the crystalline fraction and the Iam peak corresponds to the amorphous fraction (Wang et al 2006).…”
Section: Determination Of Crystallinity Index (Cri)mentioning
confidence: 99%
“…For example, during hydrolysis in hot-compressed water (HCW), the hydrolysis reactions of amorphous cellulose is considerably faster than for crystalline cellulose (Yu and Wu 2011;Yu and Wu 2010). For enzymatic hydrolysis of microcrystalline cellulose, it has also been reported that the lower cellulose CrI, the higher will be the sugar yield and the faster will be the hydrolysis reaction rate (Fan et al 1981;Peng et al 2013;Wang et al 2006). However, besides the intrinsic crystalline structure of microcrystalline cellulose, the availability of enzymes is also an important factor that determines the reaction rate of enzymatic hydrolysis of microcrystalline cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…The role of crystallinity during enzymatic hydrolysis is still controversial and may not directly explain the slowdown of the reaction. Chen et al [33] and Wang et al [35] found only a slight increase of conversion whereas some authors did not find any increase of the crystallinity index [14,36]. Other techniques were recently used to characterize nanometer changes in cellulose structure such as smallangle X-ray scattering (SAXS) [36] or small-angle neutron scattering (SANS) [37] which are suitable for the interface characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Evolution of the cellulose surface morphology was recently investigated by SANS [38] which has the advantage to be a non-destructive and more penetrating technique than SAXS. This was also investigated by scanning electron microscopy (SEM) and results showed a clear decrease in the length of cotton linters and a non-uniformity of particle size after several hours of enzymatic hydrolysis [29,35]. Using Fiber Quality Analyser Park et al [39] showed a clear decrease in particle size and other authors [3,37] correlated the particles size decrease to the increase in surface area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation